Meningkatkan Argumentasi Ilmiah melalui Integrasi Argument-Driven Inquiry dan STEM dalam Lembar Kerja Elektronik untuk Pendidikan Sains Menengah - Ade Rizka Fitria; Neni Hasnunidah; Noor Fadiawati; Agus Suyatna (Jurnal Penelitian Pendidikan IPA, 2025)
This study explores the integration of the Argument-Driven Inquiry (ADI) model with a STEM (Science, Technology, Engineering, and Mathematics) approach in interactive e-worksheets to enhance students' scientific argumentation in food biotechnology education. Using a quasi-experimental pretest-posttest design, 60 ninth-grade students from SMPN 1 Tanjung Bintang were assigned to either an experimental group, using ADI-STEM e-worksheets, or a control group, using conventional printed worksheets. Data were collected through a validated open-ended test assessing scientific argumentation components: claims, data, warrants, and backing. Analysis of N-Gain scores, t-tests, and effect sizes indicated that the experimental group showed significantly greater improvement across all indicators, with a large effect size demonstrating substantial impact. The integration of ADI and STEM not only fostered deeper cognitive engagement but also improved students' ability to form structured, evidence-backed arguments. These findings highlight the potential of combining inquiry-based learning with interdisciplinary STEM content in digital formats to enhance higher-order thinking and scientific reasoning. The study contributes to 21st-century science education and calls for further research on its long-term and broader effects.